Influence of maternal nutrition on outcome of pregnancy: prospective cohort study. Issue 7206 (7th August 1999) - Mathews, Fiona; Yudkin, Patricia; Neil, Andrew
Abstract: Objective: To investigate the relations of maternal diet and smoking during pregnancy to placental and birth weights at term. Design: Prospective cohort study. Setting: District general hospital in the south of England. Participants: 693 pregnant nulliparous white women with singleton pregnancies who were selected from antenatal booking clinics with stratified random sampling. Main outcome measures: Birth and placental weights at term. Results: Placental and birth weights were unrelated to the intake of any macronutrient. Early in pregnancy, vitamin C was the only micronutrient independently associated with birth weight after adjustment for maternal height and smoking. Each ln mg increase in vitamin C was associated with a 50.8 g (95% confidence interval 4.6 g to 97.0 g) increase in birth weight. Vitamin C, vitamin E, and folate were each associated with placental weight after adjustment for maternal characteristics. In simultaneous regression, however, vitamin C was the only nutrient predictive of placental weight: each ln mg increase in vitamin C was associated with a 3.2% (0.4 to 6.1) rise in placental weight. No nutrient late in pregnancy was associated with either placental or birth weight. Conclusions: Concern over the impact of maternal nutrition on the health of the infant has been premature Maternal nutrition, at least in industrialised populations, seems to have only a small effect on placental and birth weights. Other possible determinants of fetal and placental growth should be investigated.